Maternal microchimerism in peripheral blood in type 1 diabetes and pancreatic islet β cell microchimerism - Nelson, J. Lee (National Academy of Sciences, 2007)
Maternal cells have recently been found in the circulation and tissues of mothers' immune-competent children, including in adult life, and is referred to as maternal microchimerism (MMc). Whether MMc confers benefits during development or later in life or sometimes has adverse effects is unknown. Type 1 diabetes (T1D) is an autoimmune disease that primarily affects children and young adults. To identify and quantify MMc, we developed a panel of quantitative PCR assays targeting nontransmitted, nonshared maternal-specific HLA alleles. MMc was assayed in peripheral blood from 172 individuals, 94 with T1D, 54 unaffected siblings, and 24 unrelated healthy subjects. MMc levels, expressed as the genome equivalent per 100,000 proband cells, were significantly higher in T1D patients than unaffected siblings and healthy subjects. Medians and ranges, respectively, were 0.09 (0–530), 0 (0–153), and 0 (0–7.9). Differences between groups were evident irrespective of HLA genotypes. However, for patients with the T1D-associated DQB1*0302-DRB1*04 haplotype, MMc was found more often when the haplotype was paternally (70%) rather than maternally transmitted (14%). In other studies, we looked for female islet β cells in four male pancreases from autopsies, one from a T1D patient, employing FISH for X and Y chromosomes with concomitant CD45 and β cell insulin staining. Female islet β cells (presumed maternal) formed 0.39–0.96% of the total, whereas female hematopoietic cells were very rare. Thus, T1D patients have higher levels of MMc in their circulation than unaffected siblings and healthy individuals, and MMc contributes to islet β cells in a mother's progeny.